Sororin mediates sister chromatid cohesion by antagonizing wapl. - Nishiyama, T.; Ladurner, R.; Schmitz, J.; Kreidl, E.; Schleiffer, A.; Bhaskara, V.; Bando, M.; Shirahige, K.; Hyman, A.A.; Mechtler, K.; Peters, J.M. (Cell, 2010)
Sister chromatid cohesion is essential for chromosome segregation and is mediated by cohesin bound to DNA. Cohesin-DNA interactions can be reversed by the cohesion-associated protein Wapl, whereas a stably DNA-bound form of cohesin is thought to mediate cohesion. In vertebrates, Sororin is essential for cohesion and stable cohesin-DNA interactions, but how Sororin performs these functions is unknown. We show that DNA replication and cohesin acetylation promote binding of Sororin to cohesin, and that Sororin displaces Wapl from its binding partner Pds5. In the absence of Wapl, Sororin becomes dispensable for cohesion. We propose that Sororin maintains cohesion by inhibiting Wapl's ability to dissociate cohesin from DNA. Sororin has only been identified in vertebrates, but we show that many invertebrate species contain Sororin-related proteins, and that one of these, Dalmatian, is essential for cohesion in Drosophila. The mechanism we describe here may therefore be widely conserved among different species.